The Discriminatory Potential of Modern Recruitment Trends—A Mixed-Method Study From Germany - Kroll, Esther; Veit, Susanne; Ziegler, Matthias (Frontiers in Psychology, 2021)
People from marginalized groups are often discriminated against in traditional recruitment processes. Yet as companies faced with skill shortages change their recruitment strategies, the question arises as to whether modern recruitment trends such as the use of professional social network sites, active sourcing, and recruitment assignment to external agencies are affected by implicit or explicit discrimination. In our mixed-method study, we first conducted expert interviews with different types of recruiters to explore the potential for discrimination in the modern recruitment process. We then analyzed panel data from the Institute for Employment Research (IAB) in Germany to see whether there is quantitative evidence of discrimination in modern recruitment. A content analysis of the interviews shows that active sourcing and assignment of recruitment to private agencies are potentially affected by explicit discrimination. We identified three sources of discrimination in personnel selection: recruiters’ own attitudes, explicit instructions from managers, and the recruiters’ assumptions regarding companies’ preferred candidates. The results of mixed multilevel analyses with the company as a second level resonate with the qualitative findings: companies actively approach female employees, older employees, and employees who are born in Southern/Eastern Europe less often and offer women jobs less often. The effects for gender were still significant when we included far-right voting as a moderator variable on the employee level, but the interactions were not significant. Effects for gender and older people in active sourcing were also significant and robust when controlling for income, number of children, level of school completion, and educational background. Our findings suggest that current legislation may be insufficient to protect candidates who belong to marginalized groups from discrimination in modern recruitment.